1985
DOI: 10.1136/bmj.290.6471.811
|View full text |Cite
|
Sign up to set email alerts
|

Rapid tightening of blood glucose control leads to transient deterioration of retinopathy in insulin dependent diabetes mellitus: the Oslo study.

Abstract: In a study of retinopathy during one year of tight blood glucose control 45 type I (insulin dependent) diabetics without proliferative retinopathy were randomised to receive either continuous subcutaneous insulin infusion, multiple insulin injections, or conventional insulin treatment (controls). Near

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
136
0
5

Year Published

1986
1986
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 336 publications
(163 citation statements)
references
References 16 publications
20
136
0
5
Order By: Relevance
“…Moreover, our study demonstrates that insulin therapy is independent of the BglII gene polymorphism, which is statistically significantly associated with diabetic retinopathy. This finding suggests the existence of other factors, such as differences in the ability of insulin secretion, or differences in the frequency of episodes of hypoglycemia, or adverse events associated with insulin therapy (hypoglycemia, worsening diabetic retinopathy if HbA 1c decreases rapidly; DeWitt and Hirsch 2003;Dahl-Jorgensen et al 1985).…”
Section: Discussionmentioning
confidence: 92%
“…Moreover, our study demonstrates that insulin therapy is independent of the BglII gene polymorphism, which is statistically significantly associated with diabetic retinopathy. This finding suggests the existence of other factors, such as differences in the ability of insulin secretion, or differences in the frequency of episodes of hypoglycemia, or adverse events associated with insulin therapy (hypoglycemia, worsening diabetic retinopathy if HbA 1c decreases rapidly; DeWitt and Hirsch 2003;Dahl-Jorgensen et al 1985).…”
Section: Discussionmentioning
confidence: 92%
“…The study periods lasted from a minimum of 5 weeks to a maximum of 2 years. Upon our request, the authors of the Oslo Study [17,18,23,[25][26][27][28][29] told us that the study was originally intended to last for 2 years, but was later extended to 4 years. Due to incomplete data records after 4 years, only the results from the 2 year analysis were considered for this review.…”
Section: Description Of Included Trialsmentioning
confidence: 99%
“…The role of hyperglycaemia in the development and progression of microangiopathy is controversial [25]. Previous prospective studies, which relied on less satisfactory indices of glycaemic control than HbA1 [1,26,27], have suggested a link between the onset of retinopathy and poor control, whereas improving glycaemic control in established retinopathy has shown no convincing modification of progression [21,[28][29][30]. In our study the development of retinopathy was accompanied by a rise in diastolic blood pressure, especially in males, but multiple regression analysis showed that raised diastolic blood pressure was more closely associated with raised urinary albumin concentration than with retinopathy.…”
Section: Discussionmentioning
confidence: 99%